Using simulation to assist recruitment in seasonally dependant contact centres - May, Leeanne (2014)
The weather is unpredictable and can have a large impact on the profitability of seasonal businesses, particularly if staffing requirements are highly temperature-dependent. This dissertation has developed a what-if analysis tool using simulation methodology to assist affected SMEs in determining the best case scenario for timing hiring new staff and deciding the optimum length of temporary employment contracts. A boiler maintenance company was used as a case study and the objective to create a prototype of a tool that can be used by users with minimal statistical and modelling knowledge. Publicly available data on contact centre staffing was be used, along with any internal data which was made available by the company. The findings are that contract length could be used to improve meeting targets and a solution to show impact of weather simulated call volumes.